Behavioral Variability in the Play of Children With Autism and Their Typically Developing Peers. (22nd November 2015) - Bancroft, Stacie L.; Thompson, Rachel H.; Peters, Lindsay C.; Dozier, Claudia L.; Harper, Amy M.
Abstract : Invariable or repetitive behavior is a defining feature of autism and can limit a child's exposure to varying consequences and subsequent learning opportunities. We compared the variability in play material selection between 30 children with autism and 30 typically developing children, aged 2‐8 years, across three different activities: selecting paper outfits to dress dolls, selecting beads to place on a string, and choosing marker colors for coloring shapes. Selections of materials could be varied or identical to previous selections within the session. Although there was some overlap between the two groups, children with autism were more likely to respond invariably than typically developing children. Two‐year‐old children in both groups tended to display invariable play material selection, but variability increased across increasing age groups for typical children and remained relatively stable across increasing age groups for children with autism. Implications regarding the divergence in variable behavior across children with autism and typically developing children as a function of age are discussed. Copyright © 2015 John Wiley & Sons, Ltd.